727 TINGKAT KEMAMPUAN PENGUSAHA SEKTOR INFORMAL DALAM MENGAKSES LEMBAGA PERBANKAN DI KOTA MEDAN - Taufik Ritonga; Raina Linda Sari (Ekonomi dan Keuangan, 2014)
The informal sector is very important in the scope of economic. Because this sector can absorb a lot of labor if it’s not absorbed in the formal sector. The aim of this study was to obtain an overview of the capabilities about ability of the employers informal sector to access banking institutions in the Medan city.The population is all of the employers informal sector in Medan city. Determination of the sample using purposive sampling method by 30 people. Primary data were collected through questionnaires distributed to the respondents.From the research conducted it can be concluded that the ability of the employers informal sector to access banking institutions are otherwise not well, because the average ability of the employers informal sector to access products and services banking only 48.48%.Keywords: The Employers Informal Sector, Access, BankingInstitutions